Behavioural Profile Differences Between Cats in Animal-Assisted Services (AAS) and Non-AAS Cats Using the Fe-BARQ in Flanders - Joni Delanoeije; Christel Palmyre Henri Moons; Els Helena Karel Anna Peeters; Patricia Pendry (Animals)
The engagement of cats in animal-assisted services (AAS) is increasing. This is surprising given that feline behavioural needs have been perceived as contradictory to conditions associated with AAS engagement, leading to the assumption that cats as a species are not suitable for AAS. However, important within-species variability in behavioural traits nuancing this assumption has not been addressed. Therefore, this study aimed to map the behavioural profiles of cats engaged in AAS and non-AAS cats to detect behavioural profile differences between these groups. Such differences could point to AAS cats being selected to engage in AAS based upon particular behavioural traits or, relatedly, to AAS cats coping differently with AAS features. Using a Flemish translation of the Feline Behavioural Assessment and Research Questionnaire (Fe-BARQ), cross-sectional survey data on various cats’ (N = 474) behavioural indices were collected. Using Mann–Whitney U-tests, results indicate that AAS cats significantly differed from non-AAS cats on five out of 19 behavioural subscales. Specifically, AAS cats scored higher on sociability with people, attention seeking, sociability with cats and predatory behaviour, and they scored lower on resistance to restraint. While this study did not allow for assessing explanations for these differences, findings suggest that cats in AAS may be intentionally or unintentionally selected for behavioural traits perceived as desirable for engagement in AAS. While we refrain from drawing conclusions regarding the “suitability” of cats based solely on our findings, our study contributes to the ongoing discourse surrounding critical themes around AAS-engaging cats. Furthermore, our findings provide a first indication of the reliability of a translation of a well-validated measurement tool suitable to map behavioural traits of cats in Flanders engaged in AAS.